Professionalism in Residency Training - Ann M. Gronowski PhD; Mitchell R. McGill PhD; Ronald E. Domen MD (Elsevier, 2016)
Professionalism is one of the most important competencies for physicians but is also the most difficult to teach, assess, and manage. To better understand professionalism in pathology, we surveyed practicing pathologists and pathology residents and fellows in training. We identified 12 key desirable attributes of professionalism. In addition, 8 case scenarios highlighting unprofessional behavior were presented, and results between pathologists in practice and in training were compared. No significant differences between attending pathologists and residents were identified in how these cases should be managed. Our study demonstrated remarkable concordance between practicing pathologists and residents as to what constitutes professionalism and how to manage unprofessional behavior. Our case-based approach can be a useful technique to teach professionalism to both pathologists in practice and in training.